BEYOND WORDS: EXPLORING LANGUAGE EXCHANGE AND CULTURAL CONNECTION AT SPEAK DATING 2024 IN ZHUTIAN - Yofrina Octika Gultom (INJOSEDU: International Journal of Social and Education, 2025)
Today, as the world becomes more connected, language exchange plays an important role in helping people from different cultures understand each other and build meaningful relationships. This study looked at Speak Dating 2024, an event held in Zhutian, Taiwan, and organized by Polyglot.tw and the Taimei Foundation. The event encouraged real-life use of multiple languages, supported translanguaging and promoted cultural interaction among more than 30 table leaders from various language backgrounds. A qualitative case study approach was used, with the researcher participating both as an observer and as one of the language table leaders. Data collection involved participant observation, combining field notes, direct interactions, and analysis of event materials while the researcher also served as a table leader. Language learning and cultural connection were supported through the inclusive and relaxed environment. Participants conducted multilingual interaction, overcame linguistic challenges with creativity as well as respect for each other’s language, established cross-cultural relationships through common narration, laughter, as well as non-verbal cues. Multilingual table leaders in attendance, food-themed interactions, as well as unplanned cultural performances contributed towards enhanced experience as well as cultural consciousness. However, limitations such as interaction duration per activity, environmental noise, as well as periodic language anxiety were established as well. The research concludes that non-formal language exchange activities such as Speak Dating can be instrumental in supporting global citizenship based on linguistic curiosity, cultural humility, as well as interpersonal connection. Inferences made have pedagogical applications for language instructors as well as event facilitators designing inclusive, participatory environments for language learning as well as intercultural interaction.